CONSEQUENCES OF TRANO BRAIN INJURY IN CHILDREN - Nizamov Husan Marufzhonovich; Anvarov Umarjon Tolibjon Ugli; Alikulov Nodirbek Yuldosh Ugli; Nomozov Humoyun Shavkat Ugli; Kasimov Arslanbek Atabayevich; Mamurova Mavludakhon Mirkhamzayevna (Western European Studies, 2024)
Craniocerebral injury (CCI) is a mechanical injury to the skull and intracranial contents (brain, vessels, cerebral membranes and cranial nerves).
Keywords: craniocerebral; children; cerebral membranes